Post-COVID-19 Community-Based Tourism Sustainable Development in China. Study Case of Hebian Village - QU, Mingjing; WONG, Wong Ming (Journal of Environmental Management and Tourism, 2023)
China’s tourism sector has seen the effects of the worldwide COVID-19 outbreak. Community-based tourism has arisen as a sustainable alternative to mass tourism, benefiting local communities economically while preserving the environment and cultural heritage. Using Hebian Village as a case study, this study investigates the post-COVID-19 sustainable development of CBT in China. The study employs a qualitative methodology, including field observation and semi-structured interviews with community members, tourists, and tourism experts. The findings of this study indicate that Hebian Village has the potential for the sustainable development of CBT, as it possesses unique natural and cultural resources, and its residents are ardent about promoting tourism while maintaining their traditional way of life. Inadequate crisis management, a lack of marketing and managerial skills, and restricted access to funds are all preventing the expansion of CBT in Hebian Village. The study proposes some suggestions for the development of CBT that include the crisis of COVID-19, community participation, market orientation, and government support. CBT has the potential to contribute to the sustainable development of rural regions in China, but it requires a concerted effort on the part of all stakeholders, including the government, local communities, and tourism industry actors.